TINJAUAN PEMAHAMAN KESELAMATAN DAN KESEHATAN KERJA SEBELUM PELAKSANAAN PRAKTEK LAPANGAN INDUSTRI (Studi Kasus: Mahasiswa S1 PTB Tahun Masuk 2015) - 2170-2174, Supriyanto (CIVED, 2018)
Abstract—The background of this research is the absence of subjects K3 in S1 Engineering Education Building program. Therefore, needed to know the extent to which the understanding of science K3 before students implement the Industrial Field Practice (PLI) and how the level of understanding of students’ knowledge of Occupational Safety and Health (K3).The type of this research is descriptive study. The population of this research is 63 students of Undergraduate Engineering Education Program Entrance Year 2015 active in semester of July-December 2017. While the sample of research is 33 students of Undergraduate Engineering Education Program Entry in the year 2015 semester of July-December 2017. The primary data obtained through problem disseminated to respondent, while the secondary data obtained from the number of students of Engineering Engineering Education Undergraduate Year 2015. Research instrument is a test (questions) in the form of multiple choices. The problem was given to undergraduate students of EngineeringEducation Building Program in 2015 that had not implemented the PLI. The number of questions on the test is 42 questions. Before to conduct the research, the first step is in trial test, the aim is to know the level of difficulties and different power from the questions. The revie result in understanding of Occupational Safety and Health before the implementation of Industrial Field Practice (PLI) are: 1) based on the indicators of Occupational Safety and Health (K3) understanding on self and Civil Engineering Student Worker S1 PTB UNP academic year 2015 before the Implementation of PLI was low (59,89), 2) understanding of Occupational Safety and Health (K3) on Civil Engineering Student Environment S1 PTB UNP academic year 2015 before PLI implementation was low (64,50). Keywords:Understanding, Occupational Safety and Health, Industrial FieldPractice